Who doesn’t want democracy? A multilevel analysis of elite and mass attitudes - GORMAN, Brandon (Institutional Knowledge at Singapore Management University, 2018)
Despite its global rise in popularity, a significant number of people still oppose democracy. The present study evaluates three competing theories of opposition to democracy—developmentalist, culturalist, and elitist—using a series of multilevel regression models that combine individual- and country-level variables. Results of our statistical analyses suggest that (1) country-level indicators of social, political, and economic development are unrelated to individual support for democracy; (2) macro-cultural factors have mixed effects on individual support for democracy; and (3) individual income and education have strong effects on individual support for democracy, but this relationship is mediated by country-level economic development. Specifically, we find that, in relatively underdeveloped countries, high-income individuals are more likely to oppose democracy than low-income individuals. These results suggest that economic, social, and political development do not necessarily go together, most strongly supporting elitist approaches to studying opposition to democracy.